Standardization And Phytochemical Test Of Red Betel Leaf Simplicia (Pipper Ornatum) - Riza Vetisari; Heldi Candra (Bajang Institute, 2026)
Red betel (Piper ornatum) is a medicinal plant widely utilized in traditional medicine because of its potential pharmacological properties, including antimicrobial, antioxidant, and anti-inflammatory activities. This study aimed to standardize red betel leaf simplicia and evaluate its phytochemical characteristics to determine its quality as a raw material for herbal medicinal products. An experimental laboratory study was conducted using red betel leaves processed into simplicia through harvesting, wet sorting, washing, drying, and grinding. Ethanolic extracts were prepared using maceration followed by Soxhlet extraction. Standardization was performed by evaluating non-specific parameters, including moisture content, drying loss, ash content, water-soluble extractive value, and ethanol-soluble extractive value. Thin-layer chromatography (TLC) and qualitative phytochemical screening were employed to identify the presence of major secondary metabolites. The results showed that several quality parameters complied with the Indonesian Herbal Pharmacopoeia standards, while the moisture content and drying loss exceeded the recommended limits, indicating that the drying process requires further optimization. TLC analysis successfully produced characteristic chromatographic profiles, confirming the presence of bioactive compounds in the extract. These findings suggest that red betel leaf possesses considerable potential as a source of herbal medicine; however, improvements in post-harvest handling and drying techniques are essential to produce standardized simplicia with consistent quality and safety